Pengabdian Masyarakat Berbasis Revitalisasi Syiar Islam: Meningkatkan Kualitas Keagamaan melalui Program Pembinaan Terpadu di Desa Kurusumange: Community Service Based on the Revitalization of Islamic Propagation: Improving Religious Quality through an Integrated Development Program in Kurusumange Village - Muhammad Taufan Djafri; Ahmad Syaripudin (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2024)
The Community Service Program (KKN) is a form of community service that constitutes one of the main pillars of the Tri Dharma of Higher Education. The 7th batch of STIBA Makassar carried out the KKN program in Kurusumange Village, Tanralili District, Maros Regency, recognizing the lack of religious guidance within the community. This study aimed to examine the extent to which students' roles through the KKN program provided religious guidance for the community. The implementation method for the community service program commenced with mapping the community's problems and needs using the SOAR (Strengths, Opportunities, Aspirations, Results) analysis. Based on the analysis results, the work program was formulated according to the community's needs. The programs implemented included serving as the prayer imam and preacher for Tarawih prayers, leading congregational night prayers, delivering Friday sermons, giving dawn spiritual talks, teaching at TKA/TPA (Qur'anic study groups for children), providing DIROSA (reading and writing Arabic) and Tahsīn al-Qur'an (Qur'anic recitation improvement) instruction, organizing short Islamic courses, teaching at schools, hosting a pious children's festival, conducting social activities, providing training for funeral arrangements, and serving as the prayer imam and preacher for Eid al-Fitr prayers. All these programs were successfully implemented and have shown initial results aligning with the established KKN objective of providing religious guidance for the community.